Paul de Man: Too Demanding to Dismantle Evelin Barish’s The Double Life of Paul de Man and its US Reception - Kambourov, Dimitar (International Journal of Humanities and Social Science Research, 2016)
What should we think of a biographer who admits inability to understand the ideas of the thinker she writes about? Why write a biography of someone not only dead but also proclaimed forgotten (unless one intends to resurrect him, which is not the case)? Why dig up someone’s bones only to showcase his skeleton amidst the closet’s dirty linen? Why confine oneself to the preliminary part of someone’s life – the one preceding his academic biography? Paul de Man’s recent biography by Evelin Barish raises these and more questions and eyebrows. Surprisingly, however, it has elicited a largely positive response in the US. Why were intellectuals like Louis Menand, Peter Brooks, Susan Rubin Suleiman and others so cautious and humble in their lengthy reviews? This text will suggest some possible answers.